A Phase 2a, Randomized, Crossover Trial of Gabapentin Enacarbil for the Treatment of Postherpetic Neuralgia in Gabapentin Inadequate Responders. Issue 12 (18th September 2013) - Harden, R. Norman; Freeman, Roy; Rainka, Michelle; Zhang, Lixin; Bell, Chris; Berges, Alienor; Chen, Chao; Graff, Ole; Harding, Kathleen; Hunter, Setrina; Kavanagh, Sarah; Schwartzbach, Caryl; et al.
Abstract Objective To compare the efficacy of high‐dose (3, 600 mg/day) vs low‐dose (1, 200 mg/day) oral gabapentin enacarbil (GEn) on pain intensity in adults with postherpetic neuralgia (PHN) and a history of inadequate response to ≥1, 800 mg/day gabapentin. Design Multicenter, randomized, double‐blind, crossover study (NCT00617461). Setting Thirty‐five outpatient centers in Germany and the United States. Subjects Subjects aged ≥18 years with a diagnosis of PHN. Methods During a 2‐week baseline period, subjects received open‐label treatment with 1, 800 mg/day gabapentin. Subjects who had a mean 24‐hour average pain intensity score ≥4 during the last 7 days of the baseline period were randomized to receive GEn (1, 200 or 3, 600 mg/day) for treatment period 1 (28 days), followed by GEn 2, 400 mg/day (4 days), and the alternate GEn dose for treatment period 2 (28 days). Results There was a modest but significant improvement in pain intensity scores with GEn 3, 600 mg vs 1, 200 mg (adjusted mean [90% confidence interval] treatment difference, −0.29 [−0.48 to −0.10]; P = 0.013). The difference in efficacy between doses was observed primarily in subjects who received the higher dose during treatment period 2; certain aspects of the study design may have contributed to this outcome. Plasma steady‐state gabapentin exposure during GEn treatment was as expected and consistent between treatment periods. No new safety signals or adverse event trends relating to GEn exposure were identified. Conclusions While the overall results demonstrated efficacy in a PHN population, the differences between treatment periods confound the interpretation. These findings could provide insight into future trial designs.